Flexible work arrangement practices in achieving work-life balance: a case study in semiconductor company based in Melaka / Nur Ain Syazmeen Ahmad Zaki - Ahmad Zaki, Nur Ain Syazmeen (2014)
This study is an attempt to address the relationship of flexible working arrangement practices in achieving work-life balance among employees in Semiconductor Company based in Melaka. There were 84 respondents from different category of job among executive and above level employees in respective company took part in the survey. Since the researcher had considered possibility of incomplete or unreturned questionnaire, 100 questionnaires were distributed and the researcher managed to use 84 respondents for the result findings. A questionnaire was used as the main data collection method. Pearson Coefficient Correlation analysis was used to find direction and strength of correlation between each dependent and independent variable. The result analysis showed that there is only one independent variable that has significant relationship towards work-life balance. Telecommuting and job sharing are shown not significant towards the work-life balance. The reasons why the telecommuting and job sharing is not significant have been explained detail in the conclusion. Besides that, the study shows that there is a significant relationship between flexible working hour and work-life balance. In order to encourage the future study in this area, the researcher stated a few recommendations. It highlighted the ideas to conduct better study in the future for the organization as well as for the future researchers.